2020
DOI: 10.3390/nu12082243
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation during the Perinatal and Infant Period: Effects on gut Dysbiosis and Disease

Abstract: The perinatal period is crucial to the establishment of lifelong gut microbiota. The abundance and composition of microbiota can be altered by several factors such as preterm delivery, formula feeding, infections, antibiotic treatment, and lifestyle during pregnancy. Gut dysbiosis affects the development of innate and adaptive immune responses and resistance to pathogens, promoting atopic diseases, food sensitization, and infections such as necrotizing enterocolitis (NEC). Recent studies have indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 213 publications
(369 reference statements)
1
35
0
Order By: Relevance
“…Transplacental transport enables maternal-to-foetal transmission of long-chain polyunsaturated fatty acids (such as ω-3) [ 55 ] as well as antibodies carrying microbial components originating from both commensals and pathogens [ 6 ]. Moreover, breastmilk contains long-chain polyunsaturated fatty acids [ 55 ], and probiotics may translocate from the maternal to the infant gut via the breastmilk [ 56 ]. While supplemented probiotics generally do not permanently colonise neither the mother nor the infant gut during perinatal exposure, conflicting results have been reported on long-term effects on infant gut microbiota composition [ 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental transport enables maternal-to-foetal transmission of long-chain polyunsaturated fatty acids (such as ω-3) [ 55 ] as well as antibodies carrying microbial components originating from both commensals and pathogens [ 6 ]. Moreover, breastmilk contains long-chain polyunsaturated fatty acids [ 55 ], and probiotics may translocate from the maternal to the infant gut via the breastmilk [ 56 ]. While supplemented probiotics generally do not permanently colonise neither the mother nor the infant gut during perinatal exposure, conflicting results have been reported on long-term effects on infant gut microbiota composition [ 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many species of bacteria have been identified in neonatal meconium, placenta, and amniotic fluid. The composition of the fetal microbiota may be influenced by maternal factors such as maternal conditions, eating habits, and body weight [ 21 ]. Prenatal stress has also been shown to influence the differentiation of the child’s microbiome [ 22 ].…”
Section: Probiotic Microflora Of Breast Milkmentioning
confidence: 99%
“…There have been more numerous attempts to capture changes in infant gastrointestinal microbiota following probiotic administration (e.g. bifidobacteria and/or lactobacilli) to neonates and/or their mothers 54 . Finally, Dominguez-Bello et al 55 reported on anal, oral, and skin microbiota in Caesarean-born neonates following interventional exposure to maternal vaginal fluids.…”
Section: Manipulating the Infant Pharyngeal Microbiomementioning
confidence: 99%